Assessing the function of STAS domain protein SypA in Vibrio fischeri using a comparative analysis - Thompson, Cecilia M.; Visick, Karen L. (Frontiers in Microbiology, 2015)
Colonization of the squid Euprymna scolopes by Vibrio fischeri requires biofilm formation dependent on the 18-gene symbiosis polysaccharide locus, syp. One key regulator, SypA, controls biofilm formation by an as-yet unknown mechanism; however, it is known that SypA itself is regulated by SypE. Biofilm-proficient strains form wrinkled colonies on solid media, while sypA mutants form biofilm-defective smooth colonies. To begin to understand the function of SypA, we used comparative analyses and mutagenesis approaches. sypA (and the syp locus) is conserved in other Vibrios, including two food-borne human pathogens, V. vulnificus (rbdA) and V. parahaemolyticus (sypAVP). We found that both homologs could complement the biofilm defect of the V. fischeri sypA mutant, but their phenotypes varied depending on the biofilm-inducing conditions used. Furthermore, while SypAVP retained an ability to be regulated by SypE, RbdA was resistant to this control. To better understand SypA function, we examined the biofilm-promoting ability of a number of mutant SypA proteins with substitutions in conserved residues, and found many that were biofilm-defective. The most severe biofilm-defective phenotypes occurred when changes were made to a conserved stretch of amino acids within a predicted a-helix of SypA; we hypothesize that this region of SypA may interact with another protein to promote biofilm formation. Finally, we identified a residue required for negative control by SypE. Together, our data provide insights into the function of this key biofilm regulator and suggest that the SypA orthologs may play similar roles in their native Vibrio species.